Spirituality without spirit - Borek, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
Wesley Wildman's and Kate Stockly's book Spirit Tech - The Brave New World of Consciousness Hacking and Enlightenment Engineering is an interesting compilation and analysis of current research on technologies of spiritual experience. The book offers the latest in neuroscience, very bold predictions about the development of spirituality technology, and very far-reaching conclusions about the development of religion. The authors take an interdisciplinary approach to their work, touching on neuroscience, medical engineering, psychology, religion, and ethics. They do not shy away from the big philosophical, psychological, and ethical questions, and they specifically focus on questions of authenticity, meaning, safety, and social responsibility arising from the marriage of technology and spirituality. Modern neuroscience along with engineering has already created new areas of science-faith and technology-faith relationships. Technological substitutes for spirituality are also increasingly becoming a new challenge to traditional spirituality and to religion.
Keywords: spirituality; technology; spirit tech; spiritual experience; brain; neuroscience